2016
DOI: 10.1016/j.jpeds.2015.11.055
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ T Cell Activation in Children with Hepatitis C

Abstract: Objectives To assess if peripheral T cell populations in children with chronic hepatitis C virus (HCV) infection would show evidence of activation/exhaustion and an attenuated functional response. Study design Compared with adults, children with HCV infection have a higher rate of spontaneous viral clearance. In adults, chronic HCV has been linked to T cell exhaustion. Little is known of the immune status of children with HCV. Peripheral blood mononuclear cells were isolated from 16 children with HCV (6 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Our ndings point towards IFN-γ being a key driver of CD-axSpA, since cytotoxic T cells of both CD4 and CD8 lineages respond to IFN-y [19,20], and we observed a profound IFN response gene signature by IPA. The loss of circulating naïve T cells in our subjects with CD-axSpA may also be a consequence of a chronic interferon response, as this has been observed in other conditions characterized by chronic interferon exposure such as Down's syndrome and hepatitis C infection [21,22]. Our study, though, does not address the source(s) of the elevated IFN-γ and IL-6 observed in CD-axSpA, and it remains unclear whether these cytokines are primary drivers of, or a consequence following from, the underlying pathology.…”
Section: Discussionsupporting
confidence: 56%
“…Our ndings point towards IFN-γ being a key driver of CD-axSpA, since cytotoxic T cells of both CD4 and CD8 lineages respond to IFN-y [19,20], and we observed a profound IFN response gene signature by IPA. The loss of circulating naïve T cells in our subjects with CD-axSpA may also be a consequence of a chronic interferon response, as this has been observed in other conditions characterized by chronic interferon exposure such as Down's syndrome and hepatitis C infection [21,22]. Our study, though, does not address the source(s) of the elevated IFN-γ and IL-6 observed in CD-axSpA, and it remains unclear whether these cytokines are primary drivers of, or a consequence following from, the underlying pathology.…”
Section: Discussionsupporting
confidence: 56%
“…HCV RNA testing can reliably indicate perinatal transmission; however, infants should be at least 2 months old for this test to be reliable 4, 36. Retesting at 12 months should occur to confirm chronic HCV infection and to rule out the possibility of spontaneous seroconversion, defined as the absence of detectable HCV RNA on two occasions >6 months apart,37, 38 which occurs in 25%‐40% of infants infected via perinatal transmission 4, 39. In the absence of evidence suggesting active liver disease, delaying testing until 15‐18 months of age is likely to produce the clearest results in cases of suspected perinatal transmission.…”
Section: Diagnosismentioning
confidence: 99%
“…In children with perinatal transmission, 25%‐40% may spontaneously undergo viral clearance, usually by age 2; this has been described as a resolution of neonatal HCV infection 4. Another 6%‐12% of those with chronic hepatitis C infection may clear the virus before adulthood 4, 39, 64, 65, 66. Spontaneous viral clearance, which is associated with biochemical remission of hepatitis, has been reported to occur more frequently in children with higher alanine aminotransferase levels in the first 2 years of life 30, 38, 66, 67, 68, 69, 70.…”
Section: Natural History Of Hcv Infection In Children and Adolescentsmentioning
confidence: 99%
“…The specific T-cell response, consisting of both CD4+ and CD8+ T-cells, plays a major role in controlling infection by different viruses [4], such as the measles virus [5], cytomegalovirus (CMV) [6][7][8], hepatitis C virus (HCV) [9], and HIV [10,11]. More recently, the T-cell immune response has been increasingly recognized as a key factor in controlling virus clearance and the severity of COVID-19, in addition to the humoral immune response [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%